Influence of Matrix Type on Negative Capacitance Effect in Nanogranular Composite Films FeCoZr-Insulator - Koltunowicz, T. N.; Zhukowski, P.; Fedotov, A. K.; Larkin, A. V.; Patryn, A.; Andryevskyy, B.; Saad, A.; Fedotova, J. A.; Fedotova, V. V. (Elektronika ir Elektrotechnika, 2013)
We observed an inductive contribution to impedance in granular (Fe0.45Co0.45Zr0.10)x(Al2O3)(1-x) and (Fe0.45Co0.45Zr0.10)x(PZT)(1-x) nanocomposite films deposited in Ar + O2 atmosphere. The films with x » 0.30 (in dielectric regime) demonstrated negative capacitance effect which were explained by hopping conductance of electrons over FeCoZr nanoparticles covered with complicated CoFe-oxides and embedded into dielectric matrix. In particular, at the determined conditions such a structure of nanocomposite resulted in the increase of hopping electron mean life time on nanoparticles and delay its returning jump under subjection of alternating electric field that created the possibility for positive angles of the phase shifts q and properlynegative capacitance (inductive-like contribution) effect. DOI: http://dx.doi.org/10.5755/j01.eee.19.4.1693